Strategi Pemberdayaan Usaha Mikro Kecil dan Menengah Pengrajin Olahan Hasil Laut di Kecamatan Bulak Kota Surabaya - Am'una, Karina Dora Margaretha (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
Coastal communities are still friendly with the nickname "all shortcomings". This can happen because of several factors that cause coastal communities to be less empowered in terms of social, political and economic. One of the contributing factors is the limited insight that the community has in processing and maximizing the benefits of sea catches. This research aims to analyze the Strategy of Empowering Micro, Small, and Medium Enterprises for Processed Seafood in Bulak District, Surabaya City. This research uses descriptive qualitative methods. Data collection is carried out with interview techniques, observations and documentation. The research results show that the empowerment strategy for Micro, Small and Medium Enterprises of processed sea products craftsmen in Bulak District based on five dimensions consisting of strategy as a plan, strategy as an activity, strategy as an instrument, strategy as a system and strategy as a mindset has been implemented by the Surabaya City Small and Medium Business Cooperative Service and Trade together with the People's Welfare and Economy of Bulak District through coaching carried out through activity program planning, training, socialization, technical guidance, monitoring and evaluation to increase independence, skills, and competitiveness as well as providing business capital assistance and marketing processes. The conclusion from the results of the research is the empowerment of Micro, Small and Medium Enterprises of processed seafood artisans in Bulak District can be said to be quite optimal, as evidenced through the three dimensions that have been carried out optimally. From the five dimensions, in the dimension of strategy as a system and strategy as a mindset still requires more attention from Bulak District as a facilitator and the Surabaya City Small and Medium Enterprise Cooperative and Trade Service as a policy compiler.